8 - Non-meritocratic Factors and the Recruitment Process in Oyo State Civil Service, Nigeria - Adebimpe A. Adenugba,; Omolayo Fadoju,; Ruth E. Akhuetie, (African Sociological Review, 2017)
This study focuses on non-meritocratic factors that influence recruitment process. The main purpose was to investigate the factors that influence recruitment and selection in Oyo state civil service apart from merit, and ascertain perceived consequences of non-meritocracy in the recruitment process. The survey research method was adopted; quantitative and qualitative techniques were employed in the collection of data. Results show that the dynamics of the recruitment and selection processes in Oyo State civil service are driven more by nonmeritocratic influences such as ethnicity, religion, statism, politicization etc. which have become embedded into the socio-economic and political organization/structure of Nigeria. Merit is undermined, thereby making efficiency and effectiveness difficult to achieve in the civil service. We suggest, like many others, that meritocratic principles should be firmly entrenched in the Oyo State Civil Service and that the recruitment process should be devoid of non-meritocratic factors.